2002
DOI: 10.1210/jc.2002-020970
|View full text |Cite
|
Sign up to set email alerts
|

11β-Hydroxysteroid Dehydrogenase Types 1 and 2: An Important Pharmacokinetic Determinant for the Activity of Synthetic Mineralo- and Glucocorticoids

Abstract: The 11beta-hydroxysteroid dehydrogenase (11beta-HSD) system plays a pivotal role in glucocorticoid (GC) and mineralocorticoid (MC) action. Although 11beta-HSD activities are important determinants for the efficacy of synthetic MCs and GCs, corresponding pharmacokinetic data are scanty. Therefore, we characterized 11beta-HSD profiles for a wide range of steroids often used in clinical practice. 11beta-HSD1 and 11beta-HSD2 were selectively examined in 1) human liver and kidney cortex microsomes, and 2) Chinese h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
113
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(120 citation statements)
references
References 23 publications
4
113
1
2
Order By: Relevance
“…Although we have evaluated DHD, it is possible that structurally related synthetic glucocorticoids could be generated that have even greater ability to be activated powerfully and selectively by the 11b-HSD2 enzyme. Previous reports have analysed some of the structural determinants that determine directionality of glucocorticoid conversion by the 11b-HSD enzymes (Diederich et al 2002) and this should facilitate development of additional glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we have evaluated DHD, it is possible that structurally related synthetic glucocorticoids could be generated that have even greater ability to be activated powerfully and selectively by the 11b-HSD2 enzyme. Previous reports have analysed some of the structural determinants that determine directionality of glucocorticoid conversion by the 11b-HSD enzymes (Diederich et al 2002) and this should facilitate development of additional glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…Although 11b-HSD2 activity is unidirectional for endogenous glucocorticoids, several studies have demonstrated that the substitution of a fluoride molecule at the 9a position of the glucocorticoid structure (as seen in dexamethasone (DEX)) dramatically affects the way the enzyme metabolises these steroids (Diederich et al 2002). 9a-Fluorinated steroids are less effectively oxidised (inactivated) but in addition their inactive counterparts can be reduced (converted to their active form) by the 11b-HSD2 enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…11β-HSD1 is a low-affinity reduced NADP(H)-dependent dehydrogenase-oxoreductase which is expressed in glucocorticoid responsive tissues and activates cortisone to cortisol locally. In contrast 11β-HSD2 which is a high-affinity NAD + -dependent unidirectional dehydrogenase converts cortisol into its inactive metabolite cortisone and also inactivates prednisolone in a similar fashion [14,15]. 11β-HSD2 is highly expressed in human and murine placenta throughout gestation [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…We found group differences for hydrocortisone, which can be inactivated by the enzyme 11b-hydroxysteroid dehydrogenase 2 (11b-HSD2), but not dexamethasone, a weak 11b-HSD substrate (Diederich et al, 2002). The enzymes 11b-HSD1 and 2 play a pivotal role for local, tissue-specific regulation of steroid effects (Tomlinson et al, 2004) and are expressed in the immune system (Chapman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%